Analisa Kandungan Logam Cd, Pb, Zn Dan Cu pada Tangki Ballast Kapal Niaga di Pelabuhan Kendal dan Tanjung Mas Semarang - Apriyanto Budhi Wibowo; Hugi Cerlyawati (Jurnal Maritim Polimarin, 2021)
Commercial ships are a means of transportation at sea. For ships that do not exchange ballast water accordingly, it can be dangerous for the port environment they enter. The purpose of this research is to determine the metal content in the ballast tank water of commercial ships that have not implemented ballast water exchange in the middle of the sea following the rules of the International Maritime Organization (IMO). Research on the content of heavy metals in the ballast water of commercial ships, both ferries and cargo ships docked at the port, has been carried out using the AAS (Atomic Absorption Spectroscopy) method on flame. The results showed that the Pb content in ballast water ranged from 0.004-1.65 mg/liter, Cd ranged from 0.0015-0.47 mg/liter, Cu ranged from 0.0035-0.362 mg/liter and Zn ranged from 0.0015-2.54 mg/liter. According to the Decree of the Minister of the Environment Number 51 of 2004, the metal content of Cd and Zn has exceeded the seawater quality standards for water port, namely 0.001 mg/liter and 0.1 mg/liter, while the content of Pb and Cu has not exceeded the port quality standards.